To solve this problem, we can use the rules of exponents.
When multiplying powers with the same base, we can add their exponents.
5^4 x 5^3 = 5^(4+3) = 5^7
When dividing powers with the same base, we can subtract their exponents.
5^7 / 5^2 = 5^(7-2) = 5^5
Therefore, the answer is C) 5^5.
5^4 x 5^3/5^2
A 5^3
B 1/5^9
C 5^5
D 5^9
3 answers
which expression is equivalent to 5^4x5^3/5^2
To find an equivalent expression to 5^4 x 5^3 / 5^2, we can simplify using the rules of exponents.
When multiplying powers with the same base, we can add their exponents.
So, 5^4 x 5^3 = 5^(4+3) = 5^7.
When dividing powers with the same base, we can subtract their exponents.
So, 5^7 / 5^2 = 5^(7-2) = 5^5.
Therefore, the expression 5^4 x 5^3 / 5^2 is equivalent to 5^5.
The correct answer is C) 5^5.
When multiplying powers with the same base, we can add their exponents.
So, 5^4 x 5^3 = 5^(4+3) = 5^7.
When dividing powers with the same base, we can subtract their exponents.
So, 5^7 / 5^2 = 5^(7-2) = 5^5.
Therefore, the expression 5^4 x 5^3 / 5^2 is equivalent to 5^5.
The correct answer is C) 5^5.